Wireless rotor telemetry system for health monitoring in electrical machines - Zhao, Bowen (2016)
Brushless Synchronous Generators (BLSG) are utilized for on-board power generation in marine applications. There are several critical faults (e.g. rotor field winding faults,rotating diode rectifier short circuit, shaft and bearing faults) on the rotating part of the BLSG that require close conditioning monitoring.The use of wireless technology opens up the opportunity to directly probe the rotor of the brushless machine which would otherwise require significant modifications using conventional wired monitoring system.This project aims to design a wireless rotor telemetry system which could provide an approach to directly probe the machine's internal parameters. Compared to the conventional cable-based system, this system would lower the cost while increase the system reliability.